Towards a Model of (Insider) Witness Assessments in International Crime Cases: An Experimental Vignette Study - Chlevickaitė, Gabrielė (International criminal justice review, 2024)
Trials of international crimes frequently rely on a complex type of witnesses: insiders or accomplices. While harnessing essential knowledge, insiders pose serious challenges to the decision-makers assessing their credibility. Prior research suggests that judges dismiss a sizeable proportion of insider testimony during trials of international crimes. While some reasons might lie with the witnesses, a closer look at the professional practices is warranted. This study aimed to examine the process of insider witness statement assessments by international criminal justice professionals and to analyze how they resolve the tension between the concerns about witness truthfulness and the quality of the testimony. One hundred sixty practitioners took part in an experimental vignette survey. Results of qualitative analyses demonstrate that the assessments of the witness and the statement contents are interrelated: across all experimental conditions, respondents drew inferences about the quality of the testimony based on their assessment of the witness and vice versa. Furthermore, the same indicators were given various, at times contradictory, meanings, highlighting individual differences in professional practice and the noise in decision-making.